Estimating wastewater dilution using chemical markers and incomplete flow measurements: Application to normalisation of SARS-CoV-2 measurements - Owen D. Jones; Amy J. Baldwin; Isabelle Durance; William B. Perry; Andrew Weightman (Journal of Water Process Engineering, 2026)

Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Prioritising actions over space and time in multi-habitat ecological restoration: Insights from indicator species in coastal seascapes - Ben L. Gilby; Andrew D. Olds; Michael Sievers; Maria L. Vozzo; Brittany B. Elliott; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Ashley J. Rummell; Christopher J. Henderson (Landscape and Urban Planning, 2026)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

A cross-sectional analysis of ambient fine particulate matter (PM2.5) exposure and haemoglobin levels in children aged under 5 years living in 36 countries - Daniel B. Odo; Ian A. Yang; Sagnik Dey; Melanie S. Hammer; Aaron van Donkelaar; Randall V. Martin; Guang-Hui Dong; Bo-Yi Yang; Perry Hystad; Luke D. Knibbs (Environmental Research, 2023)

A cross-sectional analysis of long-term exposure to ambient air pollution and cognitive development in children aged 3–4 years living in 12 low- and middle-income countries - Daniel B. Odo; Ian A. Yang; Sagnik Dey; Melanie S. Hammer; Aaron van Donkelaar; Randall V. Martin; Guang-Hui Dong; Bo-Yi Yang; Perry Hystad; Luke D. Knibbs (Environmental Pollution, 2023)

A flexible and efficient B ayesian implementation of point process models for spatial capture–recapture data - Wei Zhang; Joseph D. Chipperfield; Janine B. Illian; Pierre Dupont; Cyril Milleret; Perry de Valpine; Richard Bischof (Ecology, 2023)
Spatial capture–recapture (SCR) is now routinely used for estimating abundance and density of wildlife populations. A standard SCR model includes sub‐models for the distribution of individual activity centers (ACs) and for individual detections conditional on the locations of these ACs. Both sub‐models can be expressed as point processes taking place in continuous space, but there is a lack of accessible and efficient tools to fit such models in a Bayesian paradigm. Here, we describe a set of custom functions and distributions to achieve this. Our work allows for more efficient model fitting with spatial covariates on population density, offers the option to fit SCR models using the semi‐complete data likelihood (SCDL) approach instead of data augmentation, and better reflects the spatially continuous detection process in SCR studies that use area searches. In addition, the SCDL approach is more efficient than data augmentation for simple SCR models while losing its advantages for more complicated models that account for spatial variation in either population density or detection. We present the model formulation, test it with simulations, quantify computational efficiency gains, and conclude with a real‐life example using non‐invasive genetic sampling data for an elusive large carnivore, the wolverine ( Gulo gulo ) in Norway.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Seasonal and diel patterns in activity and habitat use by brook trout (Salvelinus fontinalis) in a small Newfoundland lake - D. Cote; B. Tibble; R. A. Curry; S. Peake; B. K. Adams; K. D. Clarke; R. Perry (Environmental Biology of Fishes, 2020)
Despite the challenges winter poses to salmonids inhabiting temperate and northern environments, there are relatively few studies that evaluate the factors that influence activity and habitat use during this season, particularly for lake environments that are ice-covered. This study examines brook trout depth distribution and movement (activity and range) in relation to temperature, light, and time of day across a 17-month period in a small lake in Newfoundland, Canada. Brook trout maintained elevated diurnal activity patterns throughout the year, despite seasonal changes in temperature, shifts in depth use, and prolonged, ice-induced darkness. Despite the tendency for relatively lower activity at night, brook trout remained active nocturnally, inferring a shift in foraging modes rather than a cessation of feeding. Winter movement velocities and ranges were less than other seasons but they occupied littoral areas that overlapped extensively with spring and fall core ranges. In contrast, summer core ranges of brook trout were principally comprised of areas with cooler water in the deep portion of the lake. As water temperature increased, daytime movement velocities increased in a log-linear fashion, whereas modeled nighttime movement velocity relationships with temperature were curvilinear and included the lowest movement velocities at 2–3 °C and the highest at the extremes of the occupied temperature range. The ability of brook trout to maintain diurnal activity patterns throughout a wide spectrum of environmental conditions suggests a strong behavioral and physiological capacity to adapt to their seasonally variable environment.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Methyl isonicotinate — a non-pheromone thrips semiochemical — and its potential for pest management - D. A. J. Teulon; M. M. Davidson; N. B. Perry; M. -C. Nielsen; C. Castañé; D. Bosch; J. Riudavets; R. W. H. M. van Tol; W. J. de Kogel (International Journal of Tropical Insect Science, 2017)

Attendance and nursing patterns of harp seals in the harsh environment of the northwest Atlantic - Elizabeth A. Perry; Garry B. Stenson; Alejandro D. Buren (Polar Biology, 2017)

Mitochondrial population structure and post‐glacial dispersal of longnose sucker Catostomus catostomus in Labrador, Canada: evidence for multiple refugial origins and limited ongoing gene flow - B. L. Langille; R. Perry; D. Keefe; O. Barker; H. D. Marshall (Journal of Fish Biology, 2016)
Two hundred and eighty‐seven longnose sucker Catostomus catostomus were collected from 14 lakes in Labrador, 52 from three lakes in Ontario, 43 from two lakes in British Columbia and 32 from a lake in Yukon; a total of 414 in all. The resulting 34 haplotypes (20 in Labrador) contained moderate haplotypic diversity ( h = 0·657) and relatively low nucleotide diversity ( π = 3·730 × 10 −3 . Mean ϕ ST (0·453, P C. catostomus populations across Canada, based on province, which was validated by the analysis and spatial analysis of molecular variance ( c. 80% variation between provinces). These results probably reflect the historical imprint of recolonization from different refugia and possibly indicate limited ongoing gene flow within provinces. A haplotype network revealed one major and two minor clades within Labrador that were assigned to the Atlantic, Beringian and Mississippian refugia, respectively, with tests of neutrality and mismatch distribution indicative of a recent population expansion in Labrador, dated between c. 3500 and 8300 years ago.

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

Erratum to: Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Genome-wide association study (GWAS) of carbon isotope ratio (δ13C) in diverse soybean [Glycine max (L.) Merr.] genotypes - Arun Prabhu Dhanapal; Jeffery D. Ray; Shardendu K. Singh; Valerio Hoyos-Villegas; James R. Smith; Larry C. Purcell; C. Andy King; Perry B. Cregan; Qijian Song; Felix B. Fritschi (Theoretical and Applied Genetics, 2015)

Identification and evaluation of quantitative trait loci underlying resistance to multiple HG types of soybean cyst nematode in soybean PI 437655 - Yongqing Jiao; Tri D. Vuong; Yan Liu; Clinton Meinhardt; Yang Liu; Trupti Joshi; Perry B. Cregan; Dong Xu; J. Grover Shannon; Henry T. Nguyen (Theoretical and Applied Genetics, 2015)

Genetics and mapping of quantitative traits for nodule number, weight, and size in soybean (Glycine max L.[Merr.]) - Sadal Hwang; Jeffery D. Ray; Perry B. Cregan; C. Andy King; Marilynn K. Davies; Larry C. Purcell (Euphytica, 2014)

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Clinical and molecular epidemiology of ciprofloxacin-susceptible MRSA encoding PVL in England and Wales - M. J. Ellington; C. Perry; M. Ganner; M. Warner; I. McCormick Smith; R. L. Hill; L. Shallcross; S. Sabersheikh; A. Holmes; B. D. Cookson; A. M. Kearns (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

High-throughput genotyping with the GoldenGate assay in the complex genome of soybean - David L. Hyten; Qijian Song; Ik-Young Choi; Mun-Sup Yoon; James E. Specht; Lakshmi K. Matukumalli; Randall L. Nelson; Randy C. Shoemaker; Nevin D. Young; Perry B. Cregan (Theoretical and Applied Genetics, 2008)

Psychiatric safety of ketamine in psychopharmacology research - Edward B. Perry; Joyce A. Cramer; Hyun-Sang Cho; Ismene L. Petrakis; Laurence P. Karper; Angelina Genovese; Elizabeth O’Donnell; John H. Krystal; D. Cyril D’Souza (Psychopharmacology, 2007)

Greater vulnerability to the amnestic effects of ketamine in males - Celia J. A. Morgan; Edward B. Perry; Hyung-Sang Cho; John H. Krystal; Deepak Cyril D’Souza (Psychopharmacology, 2006)

Absence of behavioral sensitization in healthy human subjects following repeated exposure to ketamine - Hyun-Sang Cho; Deepak C. D’Souza; Ralitza Gueorguieva; Edward B. Perry; Steven Madonick; Laurence P. Karper; Anissa Abi-Dargham; Aysenil Belger; Walid Abi-Saab; Deborah Lipschitz; Alexandre Bennet; John P. Seibyl; et al. (Psychopharmacology, 2005)

Assessment of prey overlap between a native ( Polistes humilis ) and an introduced ( Vespula germanica ) social wasp using morphology and phylogenetic analyses of 16S rDNA - Marta L. Kasper; Andrew F. Reeson; Steven J. B. Cooper; Kym D. Perry; Andrew D. Austin (Molecular Ecology, 2004)
In newly invaded communities, interspecific competition is thought to play an important role in determining the success of the invader and its impact on the native community. In southern Australia, the native Polistes humilis was the predominant social wasp prior to the arrival of the exotic Vespula germanica (Hymenoptera: Vespidae) . Both species forage for similar resources (water, pulp, carbohydrate and protein prey), and concerns have arisen about potential competition between them. The aim of this study was to identify the protein foods that these wasps feed on. As many prey items are masticated by these wasps to the degree that they cannot be identified using conventional means, morphological identification was complemented by sequencing fragments of the mitochondrial 16S rRNA gene. GenBank searches using blast and phylogenetic analyses were used to identify prey items to at least order level. The results were used to construct complete prey inventories for the two species. These indicate that while P. humilis is restricted to feeding on lepidopteran larvae, V. germanica collects a variety of prey of invertebrate and vertebrate origin. Calculated values of prey overlap between the two species are used to discuss the implications of V. germanica impacting on P. humilis. Results obtained are compared to those gained by solely ‘conventional’ methods, and the advantages of using DNA‐based taxonomy in ecological studies are emphasized.

Testing the blank slate hypothesis: why honey bee colonies accept young bees - M. D. Breed; S. Perry; L. B. Bjostad (Insectes Sociaux, 2004)

RecA-Mediated, Targeted Mutagenesis in Zebrafish - Zongbin Cui; Ying Yang; Christopher D. Kaufman; Dritan Agalliu; Perry B. Hackett (Marine Biotechnology, 2003)

Adventiously-bound redox active iron and copper are at the center of oxidative damage in Alzheimer disease - George Perry; Marta A. Taddeo; Robert B. Petersen; Rudy J. Castellani; Peggy L.R. Harris; Sandra L. Siedlak; Adam D. Cash; Quan Liu; Akohiko Nunomura; Craig S. Atwood; Mark A. Smith (BioMetals, 2003)

CDP840 - M. J. Perry; J. O’Connell; C. Walker; T. Crabbe; D. Baldock; A. Russell; S. Lumb; Z. Huang; D. Howat; R. Allen; M. Merriman; J. Walls; et al. (Cell Biochemistry and Biophysics, 1998)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)